PENGEMBANGAN E-MODUL BERBASIS MODEL PEMBELAJARAN CORE UNTUK MEMFASILITASI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Khotimah Khotimah; Giyanti Giyanti; Yuni Fajriani (LPPM Universitas Bina Bangsa, 2022)
The purpose of this research was to develop E-Module teaching materials based on the CORE learning model to facilitate students' mathematical communication skills on social arithmetic subjcet. This study uses research and development methods with the ADDIE model. The results of the research were, the E-Module teaching materials based on the CORE learning model are feasible to use with a feasibility level of 91,67% coming from the media expert, 75.76% from the mathematics education expert test and 98.33% from the mathematician test. Student responses in the field test on the completeness aspect of the material were very complete (60%), attractive appearance (53.33%), good color combinations (53.33%), good language easily understood by junior high school students (53.33 %), illustrations can represent social Arithmetic material (63.33%), and E-Modules can help students learn independently (70%).